Rheological strains in concrete modified with steel fibre reinforcement - Bywalski, Czesław; KamiIński, Mieczysław (Journal of Civil Engineering and Management, 2013)
This paper discusses the rheological properties of normal (ordinary) strength concrete. The results of tests aimed at determining the creep strains and shrinkage strains in normal strength concretes modified with steel fibre reinforcement are presented. The tests were divided into three groups. Steel fibre reinforced concretes (SFRCs) with a different composition were studied in each of the groups. Hook steel fibres, 50-mm long and 0.8 mm in diameter, were used in the tested SFRCs. The latter had an average compressive strength of 35.17–59.18 MPa and a steel fibre content of 0, 25, 35, 50 and 65 kg per 1 m3 of the concrete mixture respectively. Functional dependences for the increase in shrinkage and creep strains over time are given. The problem of the effect of aggregate grading on creep strains is addressed. Conclusions concerning the rheological deformability of steel fibre reinforced concrete are drawn.